2012
DOI: 10.4238/2012.may.15.6
|View full text |Cite
|
Sign up to set email alerts
|

Methodology Multiclass microarray data classification based on confidence evaluation

Abstract: ABSTRACT. Microarray technology is becoming a powerful tool for clinical diagnosis, as it has potential to discover gene expression patterns that are characteristic for a particular disease. To date, this possibility has received much attention in the context of cancer research, especially in tumor classification. However, most published articles have concentrated on the development of binary classification methods while neglected ubiquitous multiclass problems. Unfortunately, only a few multiclass classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To our knowledge, no previous work has considered the effect of class imbalance on these coding strategies, although some have indicated that it is, in fact, harmful [33, 34]. In this paper, we proposed two solutions for this problem and used OAA coding as the baseline.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, no previous work has considered the effect of class imbalance on these coding strategies, although some have indicated that it is, in fact, harmful [33, 34]. In this paper, we proposed two solutions for this problem and used OAA coding as the baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Many research works have investigated bio-inspired computing-based approaches, in conjunction with the wrapper ideology. Hong and Cho [24] and Yu et al [61] used GA for feature selection. Wang et al [58] proposed feature selection using rough sets and particle swarm optimization (PSO).…”
Section: Related Workmentioning
confidence: 99%
“…Yu H. L. et. al used a multiclass SVM to classify multi-class microarray data with the aid of classification confidence measure [48]. And there are also some evolutionary algorithms based ensemble systems proposed to deal with this problem [32,33].…”
Section: Lorena and Carvalhomentioning
confidence: 99%